The Sesame street library, v. 5 - Frith, Michael (New York : Funk and Wagnalls, 1978)
With Jim Henson's Muppets.
Contents: Featuring the letters J and K and the number 5.
Keywords: Alphabet; Number concept; Counting; Reading